Impacts of a deep reactive layer on sedimentary phosphorus dynamics in a boreal lake recovering from eutrophication - Jilbert, Tom; Jokinen, Sami; Saarinen, Timo; Mattus-Kumpunen, Ulpu; Simojoki, Asko; Saarni, Saija; Salminen, Sarianna; Niemistö, Juha; Horppila, Jukka (Hydrobiologia, 2020)
Using biogeochemical analyses of sediments and porewaters, we investigate the legacy of a brief, intense period of eutrophication on sedimentary phosphorus (P) cycling in a boreal lake (Enonselkä basin, Lake Vesijärvi, Finland). Point-source sewage inputs in the twentieth century caused deoxygenation of the lake and accelerated the focusing of iron (Fe) and manganese (Mn) oxides into deeper areas. Early diagenesis under Fe–Mn-rich conditions now favors rapid burial of P in these areas, likely as a combination of both oxide-bound P phases and authigenic manganous vivianite. A new P budget for Enonselkä basin shows that P burial causes an annual drawdown of 1.2% (± 0.2%) of the surface sediment P inventory, supporting a long-term trend towards recovery since the construction of a wastewater treatment plant in the mid-1970s. However, remineralization of organic matter and associated dissolution of Fe–Mn oxides continues to regenerate P from a deep reactive layer (20–60 cm depth) deposited at the height of past eutrophication, leading to an upwards diffusive flux of dissolved phosphate towards the surface sediments. The magnitude of this flux is similar to that of external P loading to the lake. The combined incoming fluxes of P are likely to retard the complete recovery from eutrophication by decades, despite ongoing restoration actions.